2015
DOI: 10.1002/glia.22939
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes spatially restrict VEGF signaling by polarized secretion and incorporation of VEGF into the actively assembling extracellular matrix

Abstract: The spatial organization of vascular endothelial growth factor (VEGF) signaling is a key determinant of vascular patterning during development and tissue repair. How VEGF signaling becomes spatially restricted and the role of VEGF secreting astrocytes in this process remains poorly understood. Using a VEGF-GFP fusion protein and confocal time-lapse microscopy, we observed the intracellular routing, secretion and immobilization of VEGF in scratch-activated living astrocytes. We found VEGF to be directly transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 94 publications
2
14
0
Order By: Relevance
“…Spz family proteins and mammalian neurotrophins have been shown to be secreted proteins that can act over varying distances to induce signaling events in target cells (Parker et al 2001;Zhu et al 2008;McIlroy et al 2013;Egervari et al 2015;Harward et al 2016). To test whether Spz3 is also secreted, we transfected S2 cells with Spz3GFP, separated the cells from their conditioned media, and probed both for Spz3 expression (Supplemental Fig.…”
Section: Loss Of Normal Cortex Glial Morphology Leads To Increased Nementioning
confidence: 99%
See 1 more Smart Citation
“…Spz family proteins and mammalian neurotrophins have been shown to be secreted proteins that can act over varying distances to induce signaling events in target cells (Parker et al 2001;Zhu et al 2008;McIlroy et al 2013;Egervari et al 2015;Harward et al 2016). To test whether Spz3 is also secreted, we transfected S2 cells with Spz3GFP, separated the cells from their conditioned media, and probed both for Spz3 expression (Supplemental Fig.…”
Section: Loss Of Normal Cortex Glial Morphology Leads To Increased Nementioning
confidence: 99%
“…Mammalian neurotrophins also signal over very short distances. Evidence from astrocytes studies in vitro suggests that vascular endothelial growth factor (VEGF) is released from astrocytes in a directional manner, with subsequent accumulation in the extracellular matrix at adhesion sites for spatially restricted signaling (Egervari et al 2015). This study further suggested that VEGF secretion occurs close to its receptor, VEGFR2, for localized signaling and that the receptor undergoes constant endocytosis and recycling during signaling events.…”
Section: Cortex Glial Invasive Growth and Morphological Elaboration Amentioning
confidence: 99%
“…Indeed, its inhibition promotes human and rodent β‐cell proliferation and ameliorates pancreatic fibrosis in mice (Han et al., ; Suzuki et al., ; Dhawan et al., ). On the other hand, the release of pro‐angiogenic factors by β‐cells, such as VEGF, which is critical for the formation and vascularisation of islets and the promotion of β‐cells regeneration (Brissova et al., ), is not only produced in a soluble form, but is actively incorporated into the FN‐containing ECM scaffold by integrin‐mediated processes (Egervari et al., ). These observations suggest an important impact of FN deposition and associated growth factors, which could be modified by diabetic conditions and affect islet cells functions.…”
Section: Ecm Adhesion and Diabetesmentioning
confidence: 99%
“…Interestingly, ECM fibers are maintained under a certain viscoelastic stress, which can be sensed by cells and which is critical for maintaining a pool of ECM-bound growth factors. While enhanced forces are required to release TGF-β from ECM fibers, matrix-bound VEGF is released upon dissection of ECM-fibers [64]. This would consist of an elegant mechanism to release large amount of VEGFupon injury induced released of ECM tension.…”
Section: Fibronectincontribution To Mechanosignaling From Extracellulmentioning
confidence: 99%